Voiding disorders in elderly Egyptian women. Issue 1 (February 2015) - Torky, Haitham; El Ela, Ashraf Abo; Salah, Mohamed; Fathy, Hesham
<x xml:space="preserve">Abstract</x> Aim The aim of this work was to determine the prevalence of various lower urinary tract symptoms and the underlying urodynamic abnormalities in noninstitutionalized elderly women. Patients and methods In all, 300 elderly women aged 60 years and older were randomly selected from those attending the nonurological outpatient clinics. A total of 107 patients were later excluded from the study, either because they refused to go through the complete workup or because they had a disease or were taking medications that would affect their lower urinary tract function. The remaining 193 patients were evaluated by history, physical examination, and urodynamics. Results Thirty patients (15.54%) had no lower urinary tract symptoms, and 163 had one or more symptoms. Ninety-four patients (48.7%) complained of urinary incontinence, 38 (19.68%) of voiding difficulty, and 37 (19.17%) of dysuria. Urodynamics revealed that 96 patients (49.74%) had detrusor overactivity (DO), 63 (32.29%) had stress incontinence, 56 (29.01%) had impaired contractility, and 13 (6.73%) had sensory urgency. Conclusion Voiding dysfunctions are common in elderly women, even in those who are asymptomatic. DO was the most common dysfunction, and 38.4% of patients had more than one urodynamic abnormality. There was an association between DO and urge incontinence and between stress incontinence and urethral incompetence, but not between other symptoms and urodynamic abnormalities.